Description of a new species of Enispa Walker, 1866 (Lepidoptera: Erebidae, Boletobiinae) from Thailand - Pellinen, Markku J. (Zootaxa, 2017)
The genus Enispa Walker, 1866, type species: Enispa eosarialis Walker, 1866 [Borneo, Sarawak] (= Micraeschus Butler, 1878, type species: Hyria elataria Walker, 1861 [Sri Lanka]), contains several species, about 20 of which described and many still undescribed, some also probably misplaced. The genus occurs in Indo-Australian tropics and subtropics. Presently there are 5 species known from Borneo, with mention of several undescribed Enispa-like species (Holloway, 2009). From Thailand there are 8 species illustrated in Kononenko & Pinratana's (2013) book, 5 of which unidentified and some others, based on specimens originated from present author, which most probably are not Enispa. Nielsen & al. (1996) mentioned 7 species in Australia.